Penggunaan Metode Eksperimen Berbantuan Media Konkret Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas III SD Negeri 6 Subagan - Ni Made Suartini (Cetta: Jurnal Ilmu Pendidikan, 2019)
This study aims to improve the learning process by improving Class III Learning Outcomes of Class III Students of SD Negeri 6 Subagan Odd Semester 2017/2018 Academic Year through "The Use of Concrete Media Assisted Experimental Methods. The research of classroom action was designed in two cycles. Each cycle is carried out in four stages, namely: planning, implementation, evaluation, and reflection. The subjects of this study were third grade students of SD Negeri 6 Subagan in the year 2017/2018 in the odd semester with a total of 17 students. The object of this research is the learning outcomes of science in material objects and changes in matter. Science learning outcomes data were collected by using learning outcomes tests Data were collected using the test method. All data collected was analyzed descriptively. The criteria for success of action if the average science learning outcomes of students are at least 70 with classical completeness of at least 85%. The results of the study show that the use of concrete media assisted experimental methods can improve science learning outcomes of Class III Students of SD Negeri 6 Subagan Odd Semester 2017/2018 Academic Year. This can be seen from the results of the analysis of learning outcomes data which reached 68.82 with sufficient categories in the first cycle and then in the second cycle an increase of 12.36 to 81.18 with a good category. In addition, learning completeness increased by 29.42% from 64.70% to 94.12%. Based on these results, it can be concluded that the use of an experimental method assisted with concrete media can improve the science learning outcomes of third grade students of SD Negeri 6 Subagan in the odd semester of the 2017/2018 school year and some suggestions can be recommended: 1) To increase student learning ) To the teachers to try to manage learning by selecting and using relevant media, 3) To the school especially the headmaster to be more motivating and provide the widest opportunity for teachers in managing learning as effectively as possible by utilizing innovative learning media and relevant in creating a conducive learning atmosphere.